An Analysis of Environment’s Impact on Health - Dr. Gargi (International Journal of Engineering and Management Research, 2020)
The current body of information on how environmental exposures affect human health reflects advances in social science and medicine as well as in general technological, social, and economic growth. Human health and welfare largely depend on maintaining and defending the integrity of natural systems, including those that support life in the natural environment and reduce human impact that has a detrimental effect on ecologically sustainable development, such as clean air, safe water, biodiversity, toxic waste management, and proper land reform. Numerous scientific studies have been conducted to shed light on environmental health issues, but few studies have examined the economically significant effects of environmental change on communicable and non-communicable diseases. As a result, this review study has examined a few studies from 1990 to 2018 in an effort to pinpoint the areas of environmental health and economic challenges in South Asia and India where there are research gaps. More importantly, policymakers lack a nationally representative economic analysis of how environmental factors (such as air pollution, water resource management, toxic pollutants, and biodiversity loss) affect human infectious and non-infectious diseases, and researchers in India have not yet explored this topic. Furthermore, no scientific papers based in India have been found to have been published regarding the relationship between climate change and undernourishment, the rate of chemical exposure to human health, and human stress, including psychosocial factors. The creation and implementation of climate policies in developing countries in conjunction with universal health coverage might benefit from obtaining these under-researched literatures.